The Justice System Perspective in Criminal Law Policy on the Obligations and Responsibilities of Parents to Prevent Child - Oemar, Hafiz Alif; Riza, Faisal (Al-Risalah, 2026)
Crimes committed by children need to be addressed through legal obligations and responsibilities in the care, guidance, and supervision of children. Criminal law policies for crimes committed by children need to be made an integral part of the criminal justice system. Therefore, an in-depth legal study is needed to understand the Criminal Law Policy on Parental Obligations and Responsibilities in Preventing Child Crime. This study uses a normative legal research method with a legal approach, a review of the National Criminal Code and the Child Protection Law. The results of the study indicate that the regulation of parental obligations and responsibilities in criminal law policies has not been formulated systematically and integrated, so its effectiveness is limited in preventing child crime. It is concluded that the importance of reformulating criminal law policies oriented towards a preventive and restorative approach, prioritizing the principle of the child's best interests. This study is limited to criminal law threats related to parental obligations and responsibilities in preventing child crime.